MEGALITIK DAN CERITA RAKYAT SUKU BAHAM DI GUA SOSOSRAWERU FAK-FAK (Megalithic and Folklore of Baham Tribe in the Sosoraweru Cave Fak-Fak) - Maryone, Rini (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2014)
Megalith Papua is the actual activity with medium natural stones such as stalagmites and stalagtik in a cave, a dolmen, stone sculptures and other natural stones are considered to be the reincarnation of the spirits of ancestors, as found in the cave Sosoreweru. In this study conducted in the Cave Sosoraweru Forir village in the district of Coke, Fakfak. The methods used in this study is the method of data collection includes library research, field surveys, using the approach Ethnoarchaeology. The results of the study in the form of 4 pieces shaped stone menhirs. based on these findings may reveal molar tribal folklore in the village district Forir the consortium. Folklore have utility in a common life, as a means of educators, entertainment, social protest and the projection of a pent-up desire.ABSTRAKMegalitik Papua merupakan kegiatan aktual dengan media batu-batu alam seperti stalagmit dan stalagtik dalam gua, dolmen, batu pahatan dan batu-batu alam lainnya yang dianggap sebagai jelmaan roh-roh nenek moyang. Penelitian ini dilakukan di Gua Sosoraweru, Kampung Forir di Distrik Kokas, Kabupaten Fakfak. Adapun metode yang digunakan dalam penelitian ini adalah metode pengumpulan data yang meliputi studi pustaka, survei lapangan, dan analisis menggunakan pendekatan etnoarkeologi. Hasil penelitian berupa empat buah batu berbentuk menhir. Berdasarkan temuan tersebut dapat mengungkapkan cerita rakyat suku Baham di Kampung Forir, Distrik Fakfak. Cerita rakyat mempunyai fungsi sebagai media pendidikan, hiburan, protes sosial dan proyeksi suatu keinginan yang terpendam.